Huge aneurysmal fistula from left main artery to right atrium in a man with atypical chest pain and dyspnea on exertion. (8th March 2019) - Bayat, Fariba; Baghaei, Ramin; Safi, Morteza; Aval, Zahra Ansari; Khaheshi, Isa; Naderian, Mohammadreza
We present a 33-year-old man with atypical chest pain and with no significant past medical history. The patient was finally diagnosed as a case of huge fistula from the left main coronary artery to the right atrium, a very rare condition with challenging diagnostic and therapeutic approaches. The majority of cases of coronary artery fistula are small, asymptomatic and clinically undetectable; they frequently do not cause any complications and can spontaneously resolve. However, larger fistulas are frequently three times the size of a typical caliber of a coronary artery and may or may not cause symptoms or complications.